PS01.078: AN UNUSUAL PRESENTATION OF BOERHAAVE SYNDROME. (14th September 2018) - Annalisa Ng, Ya-Lyn; Lee, June; Lin, Jinlin; Siong Ching, Siok; Yih Andrew Wong, Siang
Abstract: Background: Oesophageal perforations are rare but potentially lethal. Boerhaave syndrome classically results in a longitudinal oesophageal perforation at the left posterolateral distal oesophagus. We present an unusual case with cervical oesophageal mucosal perforation and submucosal dissection. Methods: We review our patient—a 53 year old lady, Mdm S, who presented after 4 days of vomiting with sepsis and diabetic ketoacidosis. CT thorax scan showed extensive long segment circumferential mural thickening and oedema of the entire oesophagus, extensive pneumotosis of the proximal half, and a focal mucosal discontinuitiy of the cervical oesophagus. There were also pneumomediastinum, fat stranding in the superior mediastinum, and a right pleural effusion. Results: Gastroscopy and surgical exploration of the right hemithorax and neck identified a 2cm linear cervical oesophageal mucosal defect. There was no muscular perforation; an air leak test did not demonstrate a transmural perforation. Copious lavage of the mediastinum and right thoracic cavity were performed and large bore drains were placed in the neck, right thoracic cavity and superior mediastinum. A venting gastrostomy and a feeding jejunostomy were also created. Mdm S's recovery was complicated by a persistent right pneumothorax. An interval gastroscopy revealed a line of interrupted longitudinal oesphageal mucosal defects starting at 18cm to 31 cm from the incisors. The submucosal space had opened up for the same length, and the scope easily entered the submucosal plane, where a muscle wall defect was detected at 18cm from the incisors. Conclusion: Cervical oesophagus is an unusual site of Boerhaave's perforation. While the initial perforation was not transmural, surgical lavage and drainage were essential for sepsis control. Subsequent recovery was achieved by following principles of fistula management- diversion of gastrointestinal contents, drainage of oesophageal leak to control sepsis, optimisation of nutrition via a feeding jejunostomy. Disclosure: All authors have declared no conflicts of interest.